On the Transfer Value of Gratitude - Oded Stark; Ita Falk (Reforming the Welfare State, 1997)
The literature on private transfers tends to differentiate between two main transfer motives: exchange and altruism (for a recent review see Laitner [1997]; for a recent empirical analysis see Cox and Rank [1992]). An exchange-driven transfer is positively correlated with the income of the recipient; a recipient is better equipped to provide a service (for example, insurance or support) to a donor when the recipient's income is higher. A higher anticipated return then prompts a higher transfer. This reasoning implicitly assumes the recipient's willingness to provide a service. An altruism-driven transfer is negatively correlated with the income of the recipient. The donor cares about the recipient's well-being. A decline in this well-being prompts an infusion of support aimed at raising the recipient's income and consumption. This reasoning explicitly assumes that the donor's attitude toward the recipient is parameterized by an altruism coefficient attached to the recipient's utility in the donor's utility function, and implicitly assumes that the recipient's attitude toward the donor is given; indeed, that in the donor's mind or heart it plays no role whatsoever.
Keywords: 330; Marginal Utility; Expected Utility; Gift Exchange; Private Transfer; Initial Income